ANALISIS PRIVAT DAN SOSIAL USAHA TANI PADI DI KABUPATEN GROBOGAN - ERNOIZ ANTRIYANDARTI; SUSI WURI ANI; MINAR FERICHANI (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
Central Java is one of the producers of the national rice with1.427.101Ha harvested area and production amounted to 8.021.511 ton milled rice. Rice is the major crop in Central Java as well as the principal livelihoods. Despite the shift of labor from agriculture to other sectors, total employment in Central Java who works in the agricultural sector reached more than 37%.